Analysis of Student Satisfaction in Academic Services as Part of Quality Insurance in University - Nurul Fitriyah Sulaeman; Atin Nuryadin; Zeni Haryanto; Astrid Alifkalaila; Iyar Anjas Oktaba (Vidya Karya, 2021)
In the context of university quality insurance, student satisfaction became one of the main indicators of service success given by the institution. Measurement of student satisfaction became an invaluable input for the institution to determine the direction of urgent improvement. This study aimed to describe student satisfaction with academic services and analyzed the quality of academic services to produce measurable improvement suggestions. This research involved students in the Department of Mathematics and Natural Sciences Education, Faculty of Education and Teacher Training, Mulawarman University, as the respondents, which are 165 students, representing 6 study programs selected by Stratified Random Sampling technique with the stratum length of study, which fill the online questionnaire. The instrument used is an adaptation of the Student Satisfaction Survey (SSI). The analysis results showed that the academic services in Faculty of Teacher Training and Education Mulawarman University still need to be improved because 50.9% of respondents stated satisfied, but 49.1% stated not satisfied. The level of student satisfaction by gender tends to be the same, i.e. 2.51 for male students and 2.53 for women, while based on study period and GPA tends to increase with the duration of the study period and the increasing GPA. According to Importance-Satisfaction Matrix, the quality of academic services put all dimensions in the second quadrant, which means that the dimensions of satisfaction had been quite good.Keywords: Academic Service; Quality; Student Satisfaction; University